Poetry and psychiatry : essays on early twentieth-century Russian symbolist culture - Ljunggren, Magnus (Studies in Russian and Slavic literatures, cultures and history., 2014)
In this volume, Professor Ljunggren introduces the Symbolists and their feverish expectations in detail. Theirs was a time when for a brief moment everything seemed possible. Then came the rude awakening, best described in Bely's powerful prose masterpiece Petersburg, which serves as the connective thread and recurrent point of reference throughout this collection. Written in the early 1910s, just before the world war that was to culminate in the so-called October Revolution, Bely's novel portrays the collective experience of the Symbolists as an attempted political parricide. Many of the essays included in this volume are appearing in English for the first time.